Improving The Quality Of Service Through The Role Of Tax Volunteers - razif, Razif; Putri Rais, Rany Gesta; Indrayani, Indrayani (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2022)
The state currently adopts tax collection is the Self Assessment System. Where in this system, calculating, submitting, and paying taxes is done by self. This system is done to provide confidence in depositing taxes owed based on tax laws and regulations. Society in modern times has a very rapid lifestyle change. Likewise, in doing everything he wants a relatively fast and practical process, including the fulfillment of his tax obligations, namely paying taxes and reporting SPT. This study aims to analyze the perception of individual taxpayers in filling out the SPT and the motivation of individual taxpayers towards the services provided by tax volunteers to assist in filling out the annual SPT. The research was conducted by using a questionnaire survey of individual taxpayers in Lhokseumawe city. The data in this study were collected by distributing questionnaires to 100 samples of individual taxpayers. The hypothesis testing technique used is quantitative analysis. The measuring instrument in this study was tested using validity tests, reliability tests, and normality tests. The results of this study Motivation factors have a positive and significant effect on the quality of service tax volunteers. Perception factors have no effect and are not significant on the quality of service tax volunteers. Tax Volunteer Service Quality Factors on the CSQ-8 instrument are mostly in the very satisfied.